Resolving complexity within Rattus rattus in relation to leptospirosis / Nurul Huda Mohamad Ikbal - Nurul Huda , Mohamad Ikbal (2019)
Rattus rattus is an economically important pest widely distributed throughout Peninsular Malaysia. The taxonomic problems of this species are still debated to date. Although asymptomatic, they are currently recognised as main carriers of various zoonotic diseases, inclusive of leptospirosis which represents a serious threat for human health. This species complex has huge range of morphological variations which creates difficulties in species identification. It is vital to elucidate the complexities within this species in order to discover the population structure, associated diseases’ transmission patterns, and host-pathogen relationships. This study aims to clarify the species complexities and population structure of R. rattus in Peninsular Malaysia using DNA-based molecular method. Conventional morphometrics was incorporated to examine the skull variation within R. rattus. Moreover, as a recognised carrier of leptospirosis in Malaysia, the prevalence of Leptospira spp. circulating among urban rats and the disease’s transmission patterns within the populations are utmost critical. Transcriptomics was used to determine the functional genes; to understand the adaptation of these genes in context to disease susceptibility and resistance in rats. The result from molecular data revealed a distant relationship between Southeast Asian R. rattus towards R. rattus sensu stricto and Himalayan R. rattus (up to 5.6% K2P). The presence of R. rattus cf. lineage IV sensu Aplin et al., 2011 and R. tanezumi as a valid sympatric species was also disclosed. Through skull variation analysis, only a single morphotype of R. rattus was identified throughout Peninsular Malaysia. Sexual dimorphism and ontogenetic variation were the evident of non-geographic variations. Population structure of R. rattus was investigated based on three mitochondrial markers (COI, Cyt b, D-loop) and one nuclear gene (IRBP). High level of nucleotide and haplotype diversities were detected in R. rattus from Peninsular Malaysia, indicating a high level of genetic diversity which demonstrated low population differentiation with significant p-value (p < 0.001). Besides, phylogenetic analysis of leptospiral DNA found in either kidney or liver of R. rattus revealed circulation of pathogenic L. interrogans and L. borgpetersenii in Malaysia’s house rat. The prevalence patterns (e.g. sex, age-groups, niches) were also discovered. This study reports an update of molecular evidence on rodent leptospirosis in Peninsular Malaysia and will be useful for further research in this area. It also confirms the efficiency of 16S rRNA and LipL32 for the diagnosis of leptospirosis. Due to inflammation which can cause sepsis during leptospirosis, gene expressions of four cytokines; tumor necrosis factor-α (TNF-α), interleukin (IL)-1β, IL-6, IL-10, and chemokines of macrophage inflammatory protein-1α (MIP-1α/C-C-type chemokine ligand 3, CCL3) and gamma interferon (IFN-γ)-inducible protein 10 kDa (IP-10/C-X-C-type chemokine ligand 10, CXCL10) were studied in both kidney and liver of R. rattus. Interleukin-6 was found to be expressed during the early stage in the liver of R. rattus, while all the six genes were upregulated during the late stage of leptospirosis in the kidney of R. rattus. Overall, these studies formulate a conceptual framework based on host and pathogen relationships which can lead to the formation and documentation of leptospirosis transmission patterns within R. rattus.